2022
DOI: 10.1002/ar.25130
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates subarachnoid hemorrhage‐induced early brain injury via inhibiting ferroptosis in the rat model

Abstract: Early brain injury (EBI) refers to a series of pathophysiological brain lesions that occur within 72 hr after subarachnoid hemorrhage (SAH), which is an extremely crucial factor in the poor prognosis of patients. In EBI, ferroptosis has been proven to cause neuronal death. Quercetin (QCT) is effective in deactivating reactive oxygen species (ROS), inhibiting lipid peroxidation, and even chelating iron, but its role in SAH remains unclear. In this study, the mortality rate, severity grade of SAH, brain water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results showed that the expression of GPX4 decreased and the level of lipid peroxidation increased in the brain of rats 24 h after SAH; overexpression of GPX4 could reduce lipid peroxidation, inhibit neuronal death, and then improve brain edema and neurological damage in rats [ 147 ]. In the SAH rat experiment, quercetin (QCT) downregulated TFR1 by increasing the expression of GPX4, SLC7A11 (xCT), and FPN1, thereby inhibiting neuronal ferroptosis and alleviating EBI injury [ 148 ]. Therefore, the reduction of GPX4 expression may play an important role in neuronal ferroptosis in early brain injury, while its overexpression is neuroprotective [ 147 ].…”
Section: Gpx4mentioning
confidence: 99%
“…The results showed that the expression of GPX4 decreased and the level of lipid peroxidation increased in the brain of rats 24 h after SAH; overexpression of GPX4 could reduce lipid peroxidation, inhibit neuronal death, and then improve brain edema and neurological damage in rats [ 147 ]. In the SAH rat experiment, quercetin (QCT) downregulated TFR1 by increasing the expression of GPX4, SLC7A11 (xCT), and FPN1, thereby inhibiting neuronal ferroptosis and alleviating EBI injury [ 148 ]. Therefore, the reduction of GPX4 expression may play an important role in neuronal ferroptosis in early brain injury, while its overexpression is neuroprotective [ 147 ].…”
Section: Gpx4mentioning
confidence: 99%
“…Astragaloside IV, [ 335 ] PKR inhibitor C16, [ 347 ] netrin‐1, [ 398 ] quercetin, [ 399 ] taurine, [ 400 ] puerarin, [ 345 ] an inhibitor of inducible nitrite oxide synthase L‐NIL, [ 401 ] resveratrol and selisistat, [ 348 ] cepharanthine, [ 344 ] baicalin, [ 334 ] Fer‐1, [ 333 , 402 ] and Lip‐1 [ 346 ] alleviate early brain injury after SAH through inhibiting ferroptosis ( Table 6 ).…”
Section: Pharmacological Inhibition Of Ferroptosis To Treat Nds and S...mentioning
confidence: 99%